2011
DOI: 10.1186/1471-2202-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation by soy diets or equol: Anti-depressive & anti-obesity-like influences, age- & hormone-dependent effects

Abstract: BackgroundSoy-derived isoflavones potentially protect against obesity and depression. In five different studies we examined the influence of soy-containing diets or equol injections on depression, serotonin levels, body weight gain (BW) and white adipose tissue (WAT) deposition in female Long-Evans rats at various stages of life [rats were intact, ovariectomized or experienced natural ovarian failure (NOF)].ResultsIn general, animals fed a soy-rich diet (Phyto-600) and/or administered equol (@ 5 mg/kg/day) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 54 publications
2
36
0
2
Order By: Relevance
“…The present results were similar to previous findings where feeding Long-Evans rats significantly reduced VAT weights when fed a High-Iso vs. a Low-Iso diet [20,29]. While genistein has been shown to have weight reducing and diabetic protecting properties [30], it is interesting to note that equol represents the major circulating isoflavonoid in the present study that has been shown to have beneficial weight and VAT reducing actions [19,31].…”
Section: Body Weight Gain and Vat Weightsupporting
confidence: 81%
“…The present results were similar to previous findings where feeding Long-Evans rats significantly reduced VAT weights when fed a High-Iso vs. a Low-Iso diet [20,29]. While genistein has been shown to have weight reducing and diabetic protecting properties [30], it is interesting to note that equol represents the major circulating isoflavonoid in the present study that has been shown to have beneficial weight and VAT reducing actions [19,31].…”
Section: Body Weight Gain and Vat Weightsupporting
confidence: 81%
“…As highlighted by the reports by Setchell and Clerici, Lund et al, and Blake et al, equol has recently caught the interest of researchers because of its powerful antioxidant activity and its unique molecular and biochemical messenger properties with implications in treating age-related diseases [22][23][24]. Of particular interest, equol has an affinity for estrogen receptor beta, which is abundant in keratinocytes of the epidermis and fibroblasts in the dermis, as reported by several investigators [14,[25][26][27].…”
Section: Human Skin-related Genes Modulated By: R-equol Vs Racemic Ementioning
confidence: 99%
“…Authors showed that soy diet rich in phytoestrogens and equol produced antidepressant-like efects at the same time that induces a reduction of body weight and white adipose tissue in all endocrine conditions. After the soy-rich diet, high plasmatic levels of genistein, daidzein and equol were detected in those animals that received the highest dose [65]. Unfortunately, the authors did not evaluate anxiety-like behaviors.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…After that, several doses of a diet rich in phytoestrogens (200 or 600 ppm of phytoestrogens in diet) and equol injections (5 mg/kg) were evaluated in the forced swimming test in rats under diferent endocrine conditions: intact, ovariectomized and aged rats with natural ovarian failure [65]. Interestingly, the later group resembles an animal model of "natural menopause" because rats are acyclic, and it is the only report, as far as we know, that evaluate the efect of the isolavones under this condition.…”
Section: Preclinical Studiesmentioning
confidence: 99%